A Case of Congenital Myasthenia Gravis due to ChAT Gene Mutation in a Term Neonate: A Case Report - Soufan, Maya; Soufan, Haya; Chaudhari, Kushagra; Klarr, Judith (American Journal of Perinatology Reports, 2024)
Congenital myasthenia gravis syndrome (CMS) is a rare genetic heterogeneous disorder due to abnormal neuromuscular transmission caused by several genes. CMS caused by choline acetyltransferase (ChAT) gene mutations have been reported in 53 cases since 2020, and only three of them have been identified as hemizygous mutations.A 1-day-old term neonate was transferred from the nursery to the neonatal intensive care unit on 10 L of oxygen by face mask due to respiratory distress. Family history includes two ChAT gene variants in the elder brother and carrier genes in both parents. She was transitioned to continuous positive airway pressure +5, and chest X-ray showed poor chest expansion. Sepsis workup was negative. She was intubated due to worsening respiratory distress 3 days later. She was started on pyridostigmine, and genetic testing was done, which confirmed two ChAT gene mutations present. The patient had a tracheostomy placed on day 50 and was discharged on day 94 of life on tracheostomy and G-tube, given feeding intolerance.This case illustrates the value of genetic testing in determining the type of CMS to guide management and the importance of obtaining family history to have such syndromes earlier in the differential diagnosis to initiate treatment promptly.
Keywords: congenital myasthenia gravis; neostigmine; ChAT gene; respiratory distress; c.1669 G > A p. (A557T); c.938_939del p.(F313Cfs*7)